PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI PREZI MATERI FOTOSINTESIS UNTUK MENINGKATKAN MOTIVASI BELAJAR KELAS XI - Lukna Diana; Ismul Mauludin Al habib; Hanif Rafika Putri (Postgraduate, University of Mataram, 2025)
This study aimed to develop interactive learning videos using the Prezi application on the topic of photosynthesis to improve the learning motivation of 11th-grade students at SMK Darul Muklisin, Jember. The research employed the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Data were collected through expert validation and student motivation questionnaires. Validation results from media and subject matter experts showed high feasibility, while a limited trial with 10 students indicated a significant increase in motivation scores, from 2.35 (low) to 3.52 (very high). These findings demonstrate that Prezi-based videos are effective in enhancing student motivation and facilitating understanding of complex material such as photosynthesis. In conclusion, interactive video media developed with Prezi is both feasible and effective, making it a potential innovative solution for digital-based classrooms.